2005
DOI: 10.1099/ijs.0.02914-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanaerobacter phenolicus gen. nov., sp. nov., an anaerobe that transforms phenol into benzoate via 4-hydroxybenzoate

Abstract: An anaerobic bacterium that transforms phenol and 4-hydroxybenzoate (4-OHB) into benzoate, strain LR7.2T, was isolated from a culture originating from a mixture of swamp water, sewage sludge, swine waste and soil. Cells of strain LR7.2T are Gram-positive short rods (1×2 μm) that are electron-dense when observed by electron microscopy. The optimum pH and temperature for growth and transformation activity of 4-OHB are 7·5–8·0 and 30–37 °C, respectively. The bacterium does not use sulphate, thiosulphate, nitrate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…Their close phylogenetic relationship with classical Desulfotomaculum species suggests that members of Desulfotomaculum subcluster Ih are sulfate-reducing bacteria. However, all subcluster Ih-containing cultures (including P. thermopropionicum, P. schinkii, and strains JT and JI [42a, 43]) investigated in this study exhibited no growth with sulfate, sulfite, or organosulfonates, corroborating and extending previous findings on the physiological characteristics of this group (7,22,24). Consequently, environmentally retrieved 16S rRNA genes belonging to Desulfotomaculum cluster I are not always indicative of the presence of sulfate reducers and must be carefully interpreted.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Their close phylogenetic relationship with classical Desulfotomaculum species suggests that members of Desulfotomaculum subcluster Ih are sulfate-reducing bacteria. However, all subcluster Ih-containing cultures (including P. thermopropionicum, P. schinkii, and strains JT and JI [42a, 43]) investigated in this study exhibited no growth with sulfate, sulfite, or organosulfonates, corroborating and extending previous findings on the physiological characteristics of this group (7,22,24). Consequently, environmentally retrieved 16S rRNA genes belonging to Desulfotomaculum cluster I are not always indicative of the presence of sulfate reducers and must be carefully interpreted.…”
Section: Discussionsupporting
confidence: 76%
“…With the exception of Cryptanaerobacter phenolicus (24), all previously isolated strains and cultures of subcluster Ih obtained in this study showed this unique phenotype, although the range of degradable substrates differed among strains/cultures. The physiology of the phenol degrader C. phenolicus (previously known as strain 7) has not been fully examined, and thus, it is currently unknown whether this strain can perform syntrophic substrate oxidation in cooperation with hydro- genotrophic microbes (24,31). Given their recognized phenotypes and wide occurrence in low-sulfate, methanogenic environments, descendants of the Desulfotomaculum subcluster Ih branch most likely function as non-sulfate-reducing, syntrophic degraders of organic substrates in situ.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, despite the tremendous effort to search for phenol degraders in such environments, only a few examples are known. To date, only one species, Cryptanaerobacter phenolicus, has been isolated and characterized as an anaerobe able to metabolize phenol under methanogenic conditions (16). The organism is an anaerobic bacterium that can transform phenol into benzoate in the presence of as-yet-unidentified electron donors.…”
mentioning
confidence: 99%
“…Although anaerobic degradation of phenol has been known to occur for a long time (11, 12), biochemical and genetic investigations have been limited. To date, anaerobic biodegradation and remediation studies have focused on consortia, but recently anaerobic phenol-degrading bacteria have been isolated under denitrifying (4, 37, 39, 41), iron-reducing (23), sulfidogenic (3, 5, 18), and fermentative-methanogenic conditions (10,15,21,28,42). Biodegradation of phenolic compounds under denitrifying conditions is well documented, and several bacteria have been characterized, including Azoarcus evansii, "Aromatoleum aromaticum" strain EbN1, Azoarcus sp.…”
mentioning
confidence: 99%